A DAD-type α-cyanopyrrolopyrrole photothermal material, its preparation method and application
Patent Information
- Application Number
- CN202610987202.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2046-07-03
AI Technical Summary
然而,现有的有机光热材料仍存在固体吸收光谱较窄、非辐射跃迁效率低、光/热稳定性差等问题,限制了有机小分子光热材料在太阳能驱动的水蒸发领域的应用
[0020]1、本发明的TPA-O固体粉末在808 nm激光照射下,60秒内升温至265℃,光热响应迅速,性能优于现有多数有机小分子光热材料。
Smart Images

Figure CN122502376B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic functional materials and photothermal conversion technology, specifically relating to a DAD-type α-cyanopyrrole photothermal material and its preparation method and application. Background Technology
[0002] Photothermal materials can efficiently convert solar energy into thermal energy, showing broad application prospects in fields such as seawater desalination, wastewater purification, thermoelectric conversion, and laser ignition. Among them, organic small-molecule photothermal materials have attracted widespread attention from researchers in recent years due to their structural diversity, functional tunability, and good processability. After organic molecules absorb photon energy and transition to an excited state, they dissipate the energy as thermal energy through internal transformation, vibrational relaxation, and non-radiative transitions, thus achieving photothermal conversion. However, existing organic photothermal materials still suffer from problems such as narrow solid absorption spectra, low non-radiative transition efficiency, and poor optical / thermal stability, which limit their application in solar-driven water evaporation.
[0003] For organic photothermal materials, promoting nonradiative transitions is an effective way to improve photothermal conversion efficiency. Intramolecular and intermolecular hydrogen bonds, as a type of interaction force, are widely present in biological and inorganic materials. Although hydrogen bonds are weak interactions, they greatly influence the aggregate state, physical properties, and topological structure, thus improving the optical / thermal stability of materials. Pyrrolopyrrole, as an organic chromophore with a large planar conjugated structure, has a high molar extinction coefficient and shows unique potential in the field of photothermal conversion. How to design and synthesize pyrrolopyrrole derivatives with broad-spectrum absorption and high photothermal conversion efficiency is an urgent problem to be solved. DA (Donor-Acceptor) structured photothermal materials can achieve broad-spectrum absorption (especially in the near-infrared region) and high photothermal conversion efficiency through intramolecular charge transfer (ICT) effects. The core mechanism lies in the electronic coupling between the donor and acceptor units, which reduces the band gap of the material, thereby enhancing the utilization of the infrared portion, which accounts for the largest proportion of the solar spectrum, and suppressing radiative transitions.
[0004] Therefore, this invention introduces electron-withdrawing cyano groups and electron-donating triphenylamine groups onto the pyrrolopyrrole ring, respectively, to construct electron donor-acceptor-donor (DAD) type large conjugated structure photothermal materials (TPA-S and TPA-O). Simultaneously, it optimizes the molecular configuration and energy level distribution through heteroatom-containing π-bridges (thiophene and furan), utilizes the ICT effect to reduce the molecular energy band gap, and enhances the nonradiative transition probability through intermolecular π-π interactions and the triphenylamine rotor unit, promoting nonradiative decay and photothermal conversion. Furthermore, it forms an intermolecular hydrogen bond network through NH bonds in the molecule, achieving broad-spectrum absorption, efficient nonradiative relaxation, and excellent photothermal stability, thereby improving photothermal conversion efficiency. Under simulated sunlight (1 kW·m²), the efficiency is significantly improved.–2 Under irradiation, the water vapor efficiency of the TPA-O / sponge-based interfacial water evaporation device was 99.7%, and the water evaporation rate was 1.458 kg / m³. –2 .h –1 The integration of TPA-O into a thermal power generation device with a maximum voltage of 230 mV provides an effective technical approach for its application in efficient interfacial water evaporation. Summary of the Invention
[0005] This invention addresses the existing problems of organic photothermal materials by designing a DAD-type α-cyanopyrrole photothermal material, the structural formula of which is as follows:
[0006]
[0007] Where X = O, S.
[0008] The preparation route for DAD-type α-cyanopyrrolopyrrole photothermal materials is as follows:
[0009]
[0010] The preparation method of the DAD-type α-cyanopyrrole photothermal material with high photothermal conversion efficiency described above includes the following steps:
[0011] (1) Prepare the raw materials 1.5 times the amount of 4-diphenylaminophenylboronic acid, 1 to 10 times the amount of base, and a toluene / methanol / water mixed solvent (volume ratio 3:1:1) were added to a reaction flask. Under nitrogen protection, palladium catalyst was added, and the mixture was heated to 90 °C and stirred for 6 to 12 h. After the reaction was completed, it was extracted with dichloromethane, the organic layers were combined, the solvent was removed, and the mixture was purified by column chromatography to obtain intermediate 1.
[0012] (2) Add intermediate 1 and tetrahydrofuran to the reaction flask, stir to dissolve, then add 1.5 to 2 times the amount of iodine and excess ammonia water, react at room temperature for 6 to 12 h, stop the reaction, add sodium thiosulfate until the solution becomes clear, remove tetrahydrofuran, extract with dichloromethane, combine the organic layers, dry, filter, remove the solvent, and purify by column chromatography to obtain intermediate 2.
[0013] (3) Cut the sodium into small pieces, add it to the bottle, add tert-amyl alcohol, add an iron catalyst under nitrogen protection, heat to 110 °C, and after the sodium is completely dissolved, add 0.5 times the amount of intermediate 2, and then add 0.5 to 5 times the amount of diisopropyl succinate. React for 2 to 5 h. After the reaction is finished, cool the reaction mixture to room temperature, add a large amount of alcohol solvent to precipitate the solid, then filter under reduced pressure, and wash the solid with methanol and water until the filtrate is clear. Collect the filter cake and dry it to obtain intermediate 3.
[0014] (4) Add 3, 2 to 8 times the amount of intermediate 2-(5-tert-butylbenzoxazole)acetonitrile and solvent to the reaction flask, heat to 90 °C under nitrogen protection, then add 3 to 20 times the amount of POCl3, and then heat to 100 to 140 °C. Stop the reaction after 30 min, cool the reaction solution to room temperature, add methanol to precipitate the solid, filter to obtain crude product, dissolve the crude product in dichloromethane, add methanol to precipitate the solid, and obtain the target compound TPA-X.
[0015] The palladium catalyst in step (1) is Pd(PPh3)4, Pd(PPh3)Cl2 or Pd(dppf)Cl2, preferably Pd(PPh3)4.
[0016] The alkaline aqueous solution in step (1) includes Na2CO3 aqueous solution, Cs2CO3 aqueous solution, K2CO3 aqueous solution, KOH aqueous solution or NaOH aqueous solution, preferably Na2CO3 aqueous solution.
[0017] The alcohol solvent in step (3) includes methanol, ethanol, n-propanol, isopropanol, n-butanol or n-pentanol, preferably methanol.
[0018] The solvent in step (4) includes toluene, chlorobenzene, o-dichlorobenzene, dimethylformamide, xylene or diphenyl ether, preferably o-dichlorobenzene.
[0019] As can be seen from the above technical solution, the present invention provides a DAD-type α-cyanopyrrole photothermal material and its preparation method, which has the following beneficial effects:
[0020] 1. The TPA-O solid powder of the present invention heats up to 265°C within 60 seconds under 808 nm laser irradiation, exhibiting rapid photothermal response and superior performance compared to most existing organic small molecule photothermal materials.
[0021] 2. The TPA-O solid of the present invention has a wide absorption range, with the absorption edge reaching 1300 nm.
[0022] 3. The photothermal materials (TPA-O and TPA-S) of the present invention exhibit good cyclic thermal stability under ten switching laser cycles, demonstrating excellent photothermal stability and anti-photobleaching performance.
[0023] 4. The photothermal material of this invention has excellent photothermal conversion efficiency, achieving a conversion efficiency of 1 kW·m² under simulated sunlight (1 kW·m²). -2 Under irradiation, the water evaporation rate of the TPA-O / sponge-based interfacial water evaporation device was 1.458 kg·m⁻¹. –2 .h –1 With a water evaporation efficiency of up to 99.7%, TPA-O can be used in integrated devices for thermal power generation with a maximum voltage of 230 mV. This material has potential applications in solar-driven water evaporation and thermoelectric conversion. Attached Figure Description
[0024] Figure 1 The hydrogen spectrum of TPA-O prepared in Example 1 is shown.
[0025] Figure 2 The image shows the time-of-flight mass spectrum of TPA-O prepared in Example 1.
[0026] Figure 3 The hydrogen spectrum of TPA-S prepared in Example 1 is shown.
[0027] Figure 4 The image shows the time-of-flight mass spectrum of the TPA-S prepared in Example 2.
[0028] Figure 5 The UV-Vis absorption spectra of TPA-O and TPA-S prepared in Examples 1 and 2 in dichloromethane (concentration 10). -5 M).
[0029] Figure 6 The UV-Vis absorption spectra of the TPA-O and TPA-S solid powders prepared in Examples 1 and 2 (concentration 10) are shown. -5 M).
[0030] Figure 7 The TPA-O and TPA-S solids prepared in Examples 1 and 2 were subjected to a 1 W cm⁻¹ solution. -2 Thermal cycling curves under 808 nm laser irradiation.
[0031] Figure 8 The water evaporation rate diagrams for TPA-O and TPA-S prepared in Examples 1 and 2 under simulated sunlight irradiation are shown.
[0032] Figure 9 Voltage diagrams of TPA-O and TPA-S prepared in Examples 1 and 2 under simulated sunlight irradiation. Detailed Implementation
[0033] The specific implementation of the present invention will be further described below with reference to the embodiments, but the scope of protection of the present invention is not limited to the scope described in the embodiments. Unless otherwise specified, the percentages in parentheses below are yields.
[0034] Example 1
[0035] (1) 5-bromo-2-furanaldehyde (16.5 mmol), 4-diphenylaminophenylboronic acid (24.8 mmol) and potassium carbonate (164.8 mmol) were added to a round-bottom flask, followed by the addition of 30 mL of mixed solvent (toluene / methanol / water, volume ratio 3:1:1). Under nitrogen protection, tetra(triphenylphosphine)palladium (catalytic amount) was added, heated to 90 °C and stirred for 8 h, then cooled to room temperature, extracted with dichloromethane, the organic layers were combined, the solvent was removed by rotary evaporation, and the crude product was purified by column chromatography to obtain 4.22 g of yellow solid intermediate 1-1, with a yield of 75%. 1 H NMR (500 MHz, CDCl3) δ 9.45 (s, 1H), 7.53 (dd, J =8.7, 1.7 Hz, 2H), 7.19-7.14 (m, 5H), 7.03-6.93 (m, 8H), 6.58 (dd, J = 3.8, 1.5 Hz, 1H).
[0036]
[0037] (2) Intermediate 1-1 (19.3 mmol) and 50 mL of tetrahydrofuran were added to a round-bottom flask and stirred to dissolve. Iodine (36.6 mmol) and 250 mL of ammonia were then added. The flask was sealed and reacted at room temperature for 12 h. After the reaction was completed, sodium thiosulfate was added and the mixture was stirred until the solution became clear. Tetrahydrofuran was removed by rotary evaporation under reduced pressure. Dichloromethane was added for extraction. The organic layers were combined, dried with anhydrous sodium sulfate, filtered, and the solvent was removed by rotary evaporation. The crude product was purified by column chromatography to obtain 5.82 g of yellow solid intermediate 2-1, with a yield of 90%. 1 H NMR (400 MHz, CDCl3) δ 7.62-7.56 (m, 2H), 7.38-7.31 (m, 4H), 7.20-7.10 (m, 9H), 6.62 (d, J = 3.8 Hz, 1H).
[0038]
[0039] (3) Sodium (22.0 mmol) was cut into soybean-sized pieces and placed in a 150 mL round-bottom flask. 15 mL of tert-amyl alcohol was added to the flask, followed by anhydrous ferric chloride (catalytic amount) under nitrogen protection. The mixture was heated to 110 °C until the sodium was completely dissolved. Then, intermediate 2-1 (11.0 mmol) was added, followed by diisopropyl succinate (22.3 mmol) added dropwise. The reaction was stopped after 5 h. After the reaction solution cooled, a large amount of methanol was added to precipitate the solid. The solid was filtered under reduced pressure, and the filter cake was washed with methanol and water until the filtrate was clear. The filter cake was collected and dried to obtain 1.13 g of brown solid intermediate 3-1, with a yield of 35%, which was directly used in the next step of the reaction.
[0040]
[0041] (4) Intermediate 3-1 (0.51 mmol), 2-(5-tert-butylbenzoxazole)acetonitrile (3.6 mmol), and 20 mL of anhydrous o-dichlorobenzene were added to a round-bottom flask. The mixture was heated to 90°C under nitrogen protection, followed by the addition of POCl3 (8.3 mmol), and then heated to 140 °C. The reaction was stopped after 30 min, and the reaction solution was cooled to room temperature. Methanol was added to precipitate the solid, yielding the crude product. The crude product was dissolved in dichloromethane and precipitated with ethyl acetate, finally yielding 117 mg of dark blue solid TPA-O, with a yield of 20%. 1 H NMR (400 MHz, CDCl3) δ 13.11 (s, 2H), 7.80 (d, J = 8.3 Hz,4H), 7.54 (s, br, 2H), 7.40 (d, J = 8.5 Hz, 2H), 7.33 (t, J = 7.8 Hz, 10H),7.20-7.17 (m, 14H), 7.12 (t, J = 7.3 Hz, 4H), 6.88 (s, br, 2H), 1.20 (s,18H). MALDI-TOF (%): Calcd for C 78 H 56 N8O4 [M+H] + 1146.4581, found 1146.8574.
[0042] The proton spectrum and time-of-flight mass spectrum of TPA-O are as follows: Figure 1 and Figure 2 As shown.
[0043]
[0044] Example 2
[0045] (1) 5-bromo-2-thiophenecarboxaldehyde (16.5 mmol), 4-diphenylaminophenylboronic acid (24.8 mmol) and potassium carbonate (164.8 mmol) were added to a round-bottom flask, followed by the addition of 30 mL of mixed solvent (toluene / methanol / water, volume ratio 3:1:1). Under nitrogen protection, tetra(triphenylphosphine)palladium (catalytic amount) was added, the mixture was heated to 90 °C and stirred for 12 hours. After the reaction was completed, the mixture was extracted with dichloromethane, the organic layers were combined, the solvent was removed by rotary evaporation, and the crude product was purified by column chromatography to obtain 4.69 g of yellow solid intermediate 1-2, with a yield of 80%. 1 H NMR (500 MHz, CDCl3) δ 9.85 (s, 1H), 7.71 (d, J =4.0 Hz, 1H), 7.52 (d, J = 8.2 Hz, 2H), 7.29 (t, J = 4.8 Hz, 5H), 7.14 (d, J =7.9 Hz, 4H), 7.11-7.05 (m, 4H).
[0046]
[0047] (2) Intermediate 1-2 (19.3 mmol) and 50 mL of tetrahydrofuran were added to a round-bottom flask and stirred until dissolved. Iodine (36.6 mmol) and 250 mL of ammonia were then added. The flask was sealed and reacted at room temperature for 12 h. After the reaction was complete, sodium thiosulfate was added and the mixture was stirred until the solution became clear. Tetrahydrofuran was removed by rotary evaporation under reduced pressure. The resulting solution was transferred to a separatory funnel and extracted with dichloromethane and water. The organic layers were combined, dried with anhydrous sodium sulfate, filtered, and the solvent was removed by rotary evaporation. The crude product was purified by column chromatography to give 5.44 g of yellow solid intermediate 2-2, with a yield of 90%. 1 H NMR (500 MHz, CDCl3)δ 7.55 (d, J = 4.0 Hz, 1H), 7.46-7.42 (m, 2H), 7.33-7.27 (m, 4H), 7.17-7.05(m, 9H).
[0048]
[0049] (3) Sodium (22.0 mmol) was cut into soybean-sized pieces and placed in a 150 mL round-bottom flask. 15 mL of tert-amyl alcohol was added to the flask, and then anhydrous ferric chloride (catalytic amount) was added under nitrogen protection. The mixture was heated to 110 °C. After the sodium was completely dissolved, intermediate 2-2 (11.0 mmol) was added, followed by diisopropyl succinate (20.1 mmol) added dropwise. The reaction was stopped after 5 h. After the reaction solution was cooled to room temperature, a large amount of methanol was added to precipitate the solid. The solid was filtered under reduced pressure, and the filter cake was washed with methanol and water until the filtrate was clear. The filter cake was collected and dried to obtain 1.17 g of brown solid intermediate 3-2, with a yield of 35%, which was directly used in the next step of the reaction.
[0050]
[0051] (4) Intermediate 3-2 (0.51 mmol), 2-(5-tert-butylbenzoxazole)acetonitrile (3.61 mmol) and 20 mL of anhydrous o-dichlorobenzene were added to a round-bottom flask. The mixture was heated to 90 °C under nitrogen protection, followed by the addition of POCl3 (8.3 mmol), and then heated to 140 °C. The reaction was stopped after 30 min. The reaction solution was cooled to room temperature, and methanol was added to precipitate the solid, yielding the crude product. The crude product was dissolved in dichloromethane and precipitated with ethyl acetate, finally yielding 120 mg of blue-purple solid TPA-S, with a yield of 20%. 1 H NMR (500 MHz, CDCl3) δ 12.50 (s, 2H), 7.66 (s, br,2H), 7.60 (d, J = 8.2 Hz, 4H), 7.56 (d, J = 3.9 Hz, 2H), 7.47 (d, J = 3.9 Hz,2H), 7.43 (d, J = 8.5 Hz, 2H), 7.32-7.29 (m, 8H), 7.15-7.08 (m, 16H), 1.41(s, 18H). MALDI-TOF (%): Calcd for C 76 H 58 N8O2 S2 [M+H] + 1178.4124, found1178.8000.
[0052] The proton spectrum and time-of-flight mass spectrum of TPA-S are as follows: Figure 3 and Figure 4 As shown.
[0053]
[0054] Performance testing
[0055] Select a 1 cm wide quartz cuvette and add 2 mL of a 10% concentration. -5 The ultraviolet-visible absorption spectra of dichloromethane solutions of M TPA-O and TPA-S were measured, such as... Figure 5 As shown, TPA-O and TPA-S have multiple absorption peaks in the range of 300~800 nm, with the maximum absorption peaks located at 780 nm and 758 nm, respectively, which belong to near-infrared absorption.
[0056] The absorption of TPA-O and TPA-S solid powders is further broadened, with absorption edges reaching 1300 and 1000 nm respectively, which is beneficial for absorbing more sunlight. Figure 6 As shown.
[0057] With an 808 nm laser (1 W·cm) -2 The TPA-O and TPA-S solid powders were irradiated using an infrared camera, and their temperature changes were recorded to test their photothermal conversion performance. TPA-O heated to 265 °C within 60 s, and TPA-S heated to 251 °C within 60 s. Both molecules exhibited good cyclic thermal stability after ten cycles of switching lasers. Figure 7 As shown.
[0058] Preparation of the water evaporation apparatus: First, 10 mg of TPA-O and TPA-S were dissolved in dichloromethane. A circular sponge with a diameter of 2 cm was taken, and the lower part of the sponge was immersed in the solution and dried to obtain a sponge loaded with TPA-O and TPA-S. Water was placed in a beaker, and the sponge was floated in the beaker with the side loaded with photothermal materials facing upwards. The water evaporation apparatus was then constructed. The control group consisted of a blank sponge.
[0059] Water evaporation: A xenon lamp was used as a simulated sunlight source. The sponge in the water evaporation apparatus was irradiated under sunlight intensity, while the change in water mass in the beaker was monitored using an analytical balance. Data are as follows: Figure 8 As shown, the water evaporation rate of TPA-O reached 1.458 kg·m⁻¹ within 1 hour. -2 The water evaporation efficiency is 99.7%, and the water evaporation rate of TPA-S reaches 1.209 kg·m⁻¹. -2 The water evaporation efficiency is 82.9%, indicating that TPA-O has a better interfacial water evaporation capacity than TPA-S.
[0060] Preparation of the power generation device: First, dissolve TPA-O and TPA-S separately in dichloromethane, add conductive adhesive, and stir until homogeneous. Apply the mixture dropwise to TEC1-12706 power generation plates (40 mm × 40 mm × 3.6 mm) using test tubes. Attach the power generation plates to a heat dissipation sponge and float the device on the surface of water in a beaker to construct the power generation device.
[0061] Voltage variation: Using a xenon lamp as a simulated sunlight source, the generator was illuminated under sunlight of a certain intensity, and the voltage generated was recorded by a multimeter. The data is as follows: Figure 9 As shown, after irradiation for 1 minute, the output voltage of TPA-O was 230 mV, and the output voltage of TPA-S was 209 mV, indicating that both materials have excellent thermoelectric conversion capabilities.
[0062] The above description is merely a preferred embodiment of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A DAD-type α-cyanopyrrolopyrrole photothermal material, characterized in that, The chemical structural formula is: ,X=O.
2. The method for preparing the DAD-type α-cyanopyrrolopyrrole photothermal material according to claim 1, characterized in that, The process is as follows: 。 3. The method for preparing the DAD-type α-cyanopyrrolopyrrole photothermal material according to claim 2, characterized in that, Includes the following steps: (1) Prepare the raw materials 1.5 times the amount of 4-diphenylaminophenylboronic acid, 1 to 10 times the amount of alkaline solution, and a toluene / methanol / water mixed solvent in a volume ratio of 3:1:1 were added to a reaction flask. Under nitrogen protection, a palladium catalyst was added, and the mixture was heated to 90°C and stirred for 6 to 12 h. After the reaction was completed, the mixture was extracted with dichloromethane, the organic layers were combined, the solvent was removed, and the mixture was purified by column chromatography to obtain intermediate 1. (2) Add intermediate 1 and tetrahydrofuran to the reaction flask, stir to dissolve, then add 1.5 to 2 times the amount of iodine and excess ammonia water, react at room temperature for 6 to 12 hours, stop the reaction, add sodium thiosulfate until the solution becomes clear, remove tetrahydrofuran, extract with dichloromethane, combine the organic layers, dry, filter, remove the solvent, and purify by column chromatography to obtain intermediate 2. (3) Cut the sodium into small pieces, add it to the bottle, add tert-amyl alcohol, add iron catalyst under nitrogen protection, heat to 110°C, and after the sodium is completely dissolved, add 0.5 times the amount of intermediate 2, then add 0.5 to 5 times the amount of diisopropyl succinate, react for 2 to 5 hours, then cool the reaction mixture to room temperature, add a large amount of alcohol solvent to precipitate the solid, filter under reduced pressure, and wash the solid with methanol and water until the filtrate is clear. Collect the filter cake and dry it to obtain intermediate 3. (4) Add 3, 2 to 8 times the amount of intermediate 2-(5-tert-butylbenzoxazole)acetonitrile and solvent to the reaction flask, heat to 90°C under nitrogen protection, then add 3 to 20 times the amount of POCl3, and then heat to 100 to 140°C. Stop the reaction after 30 min, cool the reaction solution to room temperature, add methanol to precipitate the solid, filter to obtain crude product, dissolve the crude product in dichloromethane, add methanol to precipitate the solid, and obtain the target compound TPA-X.
4. The method for preparing DAD-type α-cyanopyrrolopyrrole photothermal material according to claim 3, wherein the palladium catalyst in step (1) is Pd(PPh3)4, Pd(PPh3)Cl2 or Pd(dppf)Cl2.
5. The method for preparing DAD-type α-cyanopyrrolopyrrole photothermal material according to claim 3, wherein the alkaline solution in step (1) includes Na2CO3 aqueous solution, Cs2CO3 aqueous solution, K2CO3 aqueous solution, KOH aqueous solution or NaOH aqueous solution.
6. The method for preparing DAD-type α-cyanopyrrolopyrrole photothermal material according to claim 3, wherein the iron catalyst in step (3) is FeCl3, Fe2(SO4)3, FeCl2 or FeSO4.
7. The method for preparing DAD-type α-cyanopyrrolopyrrole photothermal material according to claim 3, wherein the alcohol solvent in step (3) is methanol, ethanol, n-propanol, isopropanol, n-butanol or n-pentanol.
8. The method for preparing DAD-type α-cyanopyrrolopyrrole photothermal material according to claim 3, wherein the solvent in step (4) includes toluene, chlorobenzene, o-dichlorobenzene, xylene or diphenyl ether.
9. The application of the DAD-type α-cyanopyrrolopyrrole photothermal material according to claim 1, used in a solar-driven water evaporation device, achieves a water evaporation rate of 1.458 kg·m⁻¹. -2 .h -1 Integrated devices for thermal power generation, with a maximum voltage of 230 mV.
Citation Information
Patent Citations
Electric field-induced red-light-emitting polymer taking pyrrolo-pyrrole-dione as lateral chain and preparation and application thereof
CN101580581A
Pyrrolopyrrole cyanine free radical photo-thermal material with high photo-thermal conversion efficiency as well as preparation method and application of pyrrolopyrrole cyanine free radical photo-thermal material
CN119119051A